Cloud computing and software services : theory and techniques - Mohammad Ilyas , 1953-; Syed A. Ahson (CRC Press, 2011)
Provides you with the technical understanding needed to develop and maintain state-of-the-art cloud computing and software services. This book reviews real cases and applications of cloud computing. It features illustrations that make it suitable for academic or research-oriented settings